#TITLE_ALTERNATIVE# - RIDLO ERDATA NASUTION (NIM : 13606032); Dosen Pembimbing: Dr. Djarot Widagdo; Dr. Hendri , MUHAMMAD
Boundary element method (BEM) is one of the numerical approaches which are developed for engineering problem analysis. The transformation from domain into boundary integral in the formulation of BEM requires the discretisation of the boundary only. This helps to make the modeling easier for the user and also makes the numerical computing process in this method is more quickly. More accurate result for domain values calculation is another advantage of BEM compared to domain based numerical method such as finite element method (FEM). In this final project, a two-dimensional structural analysis program based on BEM is developed. With the consideration for further development of the user friendly interface, the software is developed using C++ programming language. Several structural analysis cases are solved using the developed software and the results are validated by analytical calculation. Analyses on the models with hole and crack demonstrate the ability of the software to simulate stress concentration condition. The visualization of displacement and stress distribution is displayed using TECPLOT and compared with the distribution results of FEM calculation.